Benefits and Success of an Interdisciplinary Wellness Interest Group (iWIG) at a Modern Jesuit University - Bartos, Susan; Gordon, Mackenzie; Andersen, Catherine J.; Hunter, Kara (Building Healthy Academic Communities Journal, 2018)
Aim: To highlight the early achievements and discuss the benefits of forming an Interdisciplinary Wellness Interest Group (iWIG) on a modern Jesuit University campus. Background: While wellness programs have a place in academic communities, universal perspectives on the best way to lead Wellness initiatives is lacking. An iWIG gives a common platform to share ideas, communicate across audiences, and provide important information to the campus community about health promotion and health patterns of the campus community. Methods: After assembling the iWIG team, on-campus meetings were held with members of the interdisciplinary group. These meetings include faculty, staff, and students from various departments. The iWIG continues to meet regularly to expand and develop wellness initiatives, research opportunities and to ensure a presence on campus. Results: The iWIG has impacted many initiatives on campus, a select few which are profiled in this manuscript. The group is involved in funded research studies, has received a "Healthy Workplace" designation, and continues to expand health and wellness into various departments on campus. Conclusions: The interdisciplinary group has provided those with an interest in health and wellness with a formal platform to express ideas and implement initiatives for all individuals to better the overall well-being of the university community.